PENGELOLAAN DANA DESA BERBASIS MAQASHID SYARIAH UNTUK MEWUJUDKAN GOOD VILLAGE GOVERNANCE - Fikra, Raosdatul; Muchlis, Saiful; Jannah, Raodahtul (Universitas Islam Negeri Alauddin Makassar, 2024)
Abstract, This research aims to determine maqashid sharia-based village fund management to realize good village governance. This research was conducted in Anrang Village, Rilau Ale District, Bulukumba Regency. This research is qualitative research with a qualitative descriptive approach. The research results show that the Anrang Village government has managed village funds well and in accordance with applicable regulations. The Anrang Village Government has also complied with the five principles in the maqashid sharia concept, namely hifdz ad-din, hifdz an-nafs, hifdz al-aql, hifdz al-mal and hifdz an-nasb, seen from the findings in the field. from programs launched by the village government that lead to the welfare of village communities. Apart from that, the principles of maqashid sharia are also very helpful in realizing good village governance in the Anrang Village government. Keywords: maqashid sharia, village funds, good village governance